TERRITORIAL DIVERSIFICATION OF TECHNOLOGICAL EXCLUSION IN RURAL AREAS IN POLAND - Śmiałowski, Tomasz; Jałowiecki, Piotr; Woźniakowski, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2015)
During the transformation, after 1989 year Poland has developed more slowly than countries of the European Union in terms of economic and technological progress. With transformation from a centrally planned economy to a free market, the rate of development in our country increased significantly. In the literature disparities in access and ability to use of information technologies between inhabitants of urban and rural areas are often indicated. The paper presents research results on technological exclusion areas development in rural areas in terms of territorial in Poland in 1994-2012. The main data source were the results of household budget surveys developed every year and made available for consideration by the Central Statistical Office. Obtained results were complemented by an analysis of social diagnosis research results conducted every two years since 2000.